Eye Movement Abnormalities in Major Depressive Disorder - Takahashi, Junichi; Hirano, Yoji; Miura, Kenichiro; Morita, Kentaro; Fujimoto, Michiko; Yamamori, Hidenaga; Yasuda, Yuka; Kudo, Noriko; Shishido, Emiko; Okazaki, Kosuke; Shiino, Tomoko; Nakao, Tomohiro; et al. (Frontiers in Psychiatry, 2021)
Background: Despite their high lifetime prevalence, major depressive disorder (MDD) is often difficult to diagnose, and there is a need for useful biomarkers for the diagnosis of MDD. Eye movements are considered a non-invasive potential biomarker for the diagnosis of psychiatric disorders such as schizophrenia. However, eye movement deficits in MDD remain unclear. Thus, we evaluated detailed eye movement measurements to validate its usefulness as a biomarker in MDD. Methods: Eye movements were recorded from 37 patients with MDD and 400 healthy controls (HCs) using the same system at five university hospitals. We administered free-viewing, fixation stability, and smooth pursuit tests, and obtained 35 eye movement measurements. We performed analyses of covariance with group as an independent variable and age as a covariate. In 4 out of 35 measurements with significant group-by-age interactions, we evaluated aging effects. Discriminant analysis and receiver operating characteristic (ROC) analysis were conducted. Results: In the free-viewing test, scanpath length was significantly shorter in MDD (p=4.2×10−3). In the smooth pursuit test, duration of saccades was significantly shorter and peak saccade velocity was significantly lower in MDD (p=3.7×10−3, p=3.9×10−3 , respectively). In the fixation stability test, there were no significant group differences. There were significant group differences in the older cohort, but not in the younger cohort, for the number of fixations, duration of fixation, number of saccades, and fixation density in the free-viewing test. A discriminant analysis using scanpath length in the free-viewing test and peak saccade velocity in the smooth pursuit showed MDD could be distinguished from HCs with 72.1% accuracy. In the ROC analysis, the area under the curve was 0.76 (standard error=0.05, p=1.2×10−7, 95% confidence interval=0.67–0.85). Conclusion: These results suggest that detailed eye movement tests can assist in differentiating MDD from HCs, especially in older subjects.